Identification and validation of monocyte to macrophage differentiation-associated as a prognostic biomarker in gastric cancer - Bai, Suyang; Chen, Zhaofeng; Ji, Rui; Wang, Yuping; Zhou, Yongning; Guo, Qinghong; Qiao, Liang (Frontiers in Oncology, 2025)
BackgroundGastric cancer (GC) has a very poor prognosis as most cases are diagnosed at a late stage, which can be partially attributed to a lack of reliable diagnostic biomarkers. Our study reveals a close correlation between monocyte to macrophage differentiation-associated (MMD) and GC.MethodsWe analyzed data from The Cancer Genome Atlas (TCGA). A close association between MMD levels and the clinicopathological features of gastric cancer patients was identified using Cox regression analysis and KM plot database analysis. Bioinformatics data were validated by real-time polymerase chain reaction and western blot analysis in GC cells. The impact of MMD on GC was examined using multiple complementary assays, including colony formation assay, CCK-8 assay, cell cycle analysis, apoptosis assessment, wound healing assay, transwell assay, and subcutaneous xenograft tumor formation assay in mice.ResultsHigh levels of MMD were observed in GC tissues. MMD accelerated cell growth and metastasis, and suppressed apoptosis in GC cells. MMD inhibition significantly suppressed the growth of xenograft tumors in mice. Further studies had revealed that MMD expression was suppressed by miR-200b-3p in GC. Dual luciferase experiment indicated that MMD is a direct target gene of miR-200b-3p. MMD might play an oncogenic role in GC by acting as a direct target of miR-200b-3p.ConclusionMMD plays an oncogenic role in gastric cancer. It may serve as a potential biomarker for GC diagnosis and a therapeutic target.